2009
DOI: 10.1111/j.1751-9020.2008.00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Media, Politics and Climate Change: Towards a New Research Agenda

Abstract: Climate change is one of the most pressing issues of our time, and the media have been demonstrated to play a key role in shaping public perceptions and policy agendas. Journalists are faced with multiple challenges in covering this complex field. This article provides an overview of existing research on the media framing of climate change, highlighting major research themes and assessing future potential research developments. It argues that analysis of the reporting of climate science must be placed in the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
220
0
39

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 288 publications
(266 citation statements)
references
References 43 publications
7
220
0
39
Order By: Relevance
“…The dominance of national state actors within media-based discourse on REDD+ is consistent with the literature on media analysis, which finds official sources such as government representatives tend to get advantaged access to the news media and as a result become primary definers of key issues (Carvalho 2007;Anderson 2009). Nevertheless there is a broad representation of other stakeholders on REDD+ being heard in Indonesian media, which reflects the broad range of interests in the future of Indonesia's forests, particularly at a time when control of and access to forest resources remains largely unresolved (Moeliono 2009).…”
Section: A Variety Of Voices Some Louder Than Otherssupporting
confidence: 59%
“…The dominance of national state actors within media-based discourse on REDD+ is consistent with the literature on media analysis, which finds official sources such as government representatives tend to get advantaged access to the news media and as a result become primary definers of key issues (Carvalho 2007;Anderson 2009). Nevertheless there is a broad representation of other stakeholders on REDD+ being heard in Indonesian media, which reflects the broad range of interests in the future of Indonesia's forests, particularly at a time when control of and access to forest resources remains largely unresolved (Moeliono 2009).…”
Section: A Variety Of Voices Some Louder Than Otherssupporting
confidence: 59%
“…It is important to note that only one-third of the total organizations connected their social media networking sites to their website (Jun, 2011). Anderson (2009) found that past mass media news coverage has mainly contributed to mitigation rather than adaptation options.…”
Section: Climate-change Communicationmentioning
confidence: 99%
“…The incidence of flooding is both immediately palpable and dramatically out of the ordinary, unlike climate change, which has often depended upon other events, such as meetings of the IPCC or the international Conference of the Parties to the UN Framework Convention, to lend it news value (Anderson 2009). Flooding, by contrast, is a newsworthy event in and of itself, conforming to journalistic norms of immediacy and factualness while also satisfying the 'if it bleeds, it leads' imperative for attention-grabbing drama (Hannigan 1995).…”
Section: Patterns Of Flooding Coveragementioning
confidence: 99%